Study of Taurine Content in Energy Drink Powders: UV-Vis Spectrophotometric Method - Ramdan, Siti Rahmah Kurnia; Athollah, Rifqi Nabil; Yusuf, Anna L; Nugraha, Davit; Wahlanto, Panji (INDOGENIUS, 2025)
Background and Objective: Energy drinks are commonly consumed as a fast and affordable solution to fatigue, especially among adolescents and young adults. However, public knowledge about their appropriate use and the health risks of excessive intake remains limited. Taurine (2-aminoethanesulfonic acid), a conditionally essential amino acid found in many energy drinks, contributes to several physiological functions. Excessive intake of taurine may adversely affect kidney function. Method: The method of this study using UV-Vis spectrophotometry. A 0.1% ninhydrin solution was used for qualitative testing, while UV-Vis spectrophotometry was employed for quantitative measurement. Proteins were precipitated using Carrez I and Carrez II reagents before analysis. Results: A purplish-blue color change in the qualitative test confirmed the presence of taurine. Quantitative analysis revealed taurine concentrations of 0.025% and 0.012% in the two samples.  Conclusion: The results validate UV-Vis spectrophotometry as a practical and dependable technique for analyzing taurine, highlighting the importance of educating the public on the associated health risks of excessive consumption.